A new independent training concept for the quality assurance in the field of industrial computed tomography for dimensional metrology - Zippert, Patrick; Menoncin, Marco; Savio, Enrico; Rocha, Luis; Guerra, Helder; Hausotte, Tino (4th Dimensional X-ray Computed Tomography Conference, 2019)
Especially for dimensional measurements of industrial components, computed tomography (CT) offers many advantages. While conventional tactile or optical coordinate measuring systems (CMS) can only measure external accessible structures and features, CT also allows the measurement of hidden or internal features within one scan. This non-destructive technology allows the measurement of internal geometries of complex parts as well as the detection of defects such as cracks or voids. Due to the wide range of applications, CT is increasingly used in the industry. However, CT measurement results are strongly influenced by operator decisions on scanning parameters and system set-up. Especially in case of new measuring technologies, the operators are often the most relevant error sources, due to a lack of knowledge. Therefore, highly skilled personnel is required for the operations and management on measuring instruments as well as for the analysis and evaluation of the measurement data. Within the Erasmus+ KA2 project “European Training for Coordinate Metrology 4.0”, a new blended learning concept is under development to provide an individual, flexible training to obtain the necessary expertise. This CMS manufacturer-independent learning system is modular and structured in ten steps based on the recommended workflow to perform a coordinate measurement. A technology-specific learning path focused on CT is provided. The content is consistent with the ISO GPS matrix model and addressed to industrial operators, in particular the automotive suppliers in SMEs (Small-Medium Enterprises). It includes interactive learning modules- in five languages (German, English, French, Italian, Portuguese). In addition to the learning modules with the up-to-date knowledge in the field of CT measurements, effective workshop activities are under development to allows the participants to perform a measurement task on a real CT. The aim is to ensure sustainable quality assurance in the field of C